A rare cause of obstructive defecation in a 29-year-old woman: Ileo-colo-colonic intussusception treated by subtotal colectomy with posterior rectopexy - Kunduz, Enver (Turk J Surg, 2018)
Adult intussusception is a rare clinical condition. In majority of adult cases, there is an underlying cause such as polyps or colon cancers. In the present study, a 29-year-old woman with intermittent and colicky abdominal pain, constipation, and painful defecation, accompanied with distention and sense of rectal fullness, was evaluated with computed tomography. Ileo-colo-colic intussusception was determined. Subtotal colectomy with posterior rectopexy was performed. After the surgery, she was doing well at 13-month follow-up.